2019
DOI: 10.1002/fsn3.1021
|View full text |Cite
|
Sign up to set email alerts
|

Extraction optimization, antioxidant activity, and tyrosinase inhibitory capacity of polyphenols from Lonicera japonica

Abstract: The objective of this research was twofold: first, to optimize the extraction process of Lonicera japonica polyphenols using a response surface methodology, and second, to study the antioxidant activity and tyrosinase inhibitory capacity of the polyphenols of different purities. High‐speed shearing homogenization extraction was used to extract the polyphenols from L. japonica . The antioxidant activity and the effect of polyphenols on tyrosinase activity were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The antioxidative property of L. japonica is mainly attributed to the specific chemical structure of polyphenols, a widespread group of secondary metabolites that include various phenolic acids and flavonoids, which have a common character of having at least one aromatic ring substituted with one or more hydroxyl groups ( Kong et al, 2017 ; Fan et al, 2019 ). Lee et al (2019) who reported that the antioxidant activities of L. japonica were positively correlated with total phenolic, total flavonoid, CGA, CA, and quercetin contents, and Kong et al (2017) who reported that antioxidative activity of L. japonica presented a significant positive correlation with the content of CGA, cynaroside, rutin, and hyperoside can demonstrate this conclusion.…”
Section: Lonicera Japonica (Extracts) and Intestinal Antioxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidative property of L. japonica is mainly attributed to the specific chemical structure of polyphenols, a widespread group of secondary metabolites that include various phenolic acids and flavonoids, which have a common character of having at least one aromatic ring substituted with one or more hydroxyl groups ( Kong et al, 2017 ; Fan et al, 2019 ). Lee et al (2019) who reported that the antioxidant activities of L. japonica were positively correlated with total phenolic, total flavonoid, CGA, CA, and quercetin contents, and Kong et al (2017) who reported that antioxidative activity of L. japonica presented a significant positive correlation with the content of CGA, cynaroside, rutin, and hyperoside can demonstrate this conclusion.…”
Section: Lonicera Japonica (Extracts) and Intestinal Antioxidantmentioning
confidence: 99%
“…Plant extracts have been used for centuries in traditional medicine and as food preservatives, and more recently have been studied as possible feed additives used in animal nutrition due to their multiple biological functions ( Kim et al, 2012 ; Yejun et al, 2019 ). Lonicera japonica ( L. japonica ) extract is extracted from L. japonica Thunberg, a medicine food homologous herb rich in organic acids, volatile oils, flavonoids, iridoids, and saponins ( Shang et al, 2011 ; Fan et al, 2019 ; Li R. et al, 2020 ), which have high value of health benefits. Lonicera japonica extract is widely used in pharmacological preparations, cosmetics, food, and animal husbandry because of its diverse pharmacological effects such as antioxidant, anti-microbial, antiviral, antitoxic, antiseptic, and anti-inflammatory properties ( Kang et al, 2010 ; Park et al, 2012 ; Yejun et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extraction is the first important step to recover bioactive compounds from plants for natural product research (Mahugo et al, 2009). Many factors such as extraction temperature, liquid-to-solid ratio, extraction time, solvent composition, among others, may significantly influence the extraction efficacy (Fan et al, 2019). In general, optimization of a process can be determined by an empirical or statistical method.…”
Section: Introductionmentioning
confidence: 99%
“…This species has important potential uses in pharmaceutical preparations, cosmetics and health care products, such as toothpastes, herbal teas and food additives in beverages [4,5]. This species produces various natural bioactive compounds with effects on human health, such as antiviral and anti-inflammatory reactions [6,7,8] Additionally, these bioactive compounds can significantly enhance the immunological function of human cells and body fluids, exhibiting a high effect in aqueous solution. Previous studies have shown that L. japonica has a significant inhibitory effect on Staphylococcus aureus and Streptococcus pneumonia [9].…”
Section: Introductionmentioning
confidence: 99%